Synthesis of Stereotetrads by Regioselective Cleavage of Diastereomeric MEM-Protected 2-Methyl-3,4-epoxy Alcohols with Diethylpropynyl Aluminum - Torres, Wildeliz; Torres, Gerardo; Prieto, José A. (Synlett, 2012)
The regioselectivity of the epoxide ring opening of 2-methyl-3,4-epoxy alcohols with diethylpropynylalane has been studied as a function of the C1 alcohol protecting group. An efficient selective method was developed using MEM as the protecting group. The reaction proceeded in a highly regioselective manner providing the useful 1,3-diol motif. The undesired 1,4-diol product produced by some free alcohol diastereomers was not observed. This highly stereoselective method provides access to termini-differentiated stereotetrads, which are essential building blocks for polypropionate synthesis.
Keywords: cleavage; epoxides; aluminum; stereotetrads; 3,4-epoxy alcohols